KONSTRUKSI SEMIGRUP REGULER DENGAN TRANSVERSAL INVERS IDEAL KUASI - Thresye Thresye; Na'imah Hijriati (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2011)
A transversal inverse o S of a regular semigrup S is called a quasi ideal transversal inverse or Q-transversal inverse if o o o S SS  S where o S is the quasi ideal of S. Let S is a regular semigrup with transversal invers o S which is the quasi ideal of S. For example  o o oo R  xS: x x  x x and eg  o oo o L  aS: aa  a a, then R and L is an orthodox semigrup with transverse inverse o S which is ideal right of R and is the left ideal of L. Can be constructed regular semigrup with transversal inverse ideal quasi-shaped    o o R L  x, a  R L: x  a .It is connected with a band, then a regular semigrup with transverse inverse ideal quasi-shaped   o o R B  x, e R B: x x  e